If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -19 = -1x + -2(1 + -2x) Reorder the terms: -19 + 3x = -1x + -2(1 + -2x) -19 + 3x = -1x + (1 * -2 + -2x * -2) -19 + 3x = -1x + (-2 + 4x) Reorder the terms: -19 + 3x = -2 + -1x + 4x Combine like terms: -1x + 4x = 3x -19 + 3x = -2 + 3x Add '-3x' to each side of the equation. -19 + 3x + -3x = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 -19 + 0 = -2 + 3x + -3x -19 = -2 + 3x + -3x Combine like terms: 3x + -3x = 0 -19 = -2 + 0 -19 = -2 Solving -19 = -2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| X+(x-45)+(x-45)+(x-45)=540 | | (x+9)+(x+2)+(x-7)=180 | | 5x^3y+5x^4-15x^4y=0 | | 6y+2+(2/3)-y | | 1/9y+1/3=-1/18 | | -(7t+1)-(-6t-6)=-1 | | x-16=102 | | 8=-5x+x | | 11x-27=11x+7 | | 15=-5a+2a | | 6z+14=5z+2 | | 14x=4x+190 | | 8-3p-4=2p | | 3-81/x=12 | | 44.4/1917000 | | 3/4(16x-4)=21 | | 15=-5a+a | | 5/18a-27=-7 | | 4(-5+x)=30-6x | | 6-1.5x=-12+x | | F(c)=4x-5 | | -3a+5a=6 | | 3.7w=-11.1 | | -4x+2=-26 | | -9(1+r)=36 | | 0(0x+1)-5=10 | | 90-4t=25(180-t) | | y-1/4=-3/5 | | 4n+5n=-18 | | 333-112/4 | | 3x-19=-x-2(1-2) | | x+(-53)=89 |